2007
DOI: 10.1021/je700319x
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of the Single Gases Methane and Xenon in the Ionic Liquid [bmim][CH3SO4]

Abstract: Solubility measurements of methane and of xenon in the ionic liquid 1-n-butyl-3-methylimidazolium methyl sulfate ([bmim][CH 3 SO 4 ]) were performed with a high-pressure view-cell technique based on the synthetic method. The temperature ranged from 293.1 K to 413.2 K, and the maximum pressure (the maximum gas molality) was 8.9 MPa (0.19 mol‚kg -1 ) for methane and 11.3 MPa (0.65 mol‚kg -1 ) for xenon. Both gases become less soluble in [bmim][CH 3 SO 4 ] with rising temperature, but xenon shows a significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 17 publications
7
31
0
Order By: Relevance
“…As Figure shows, the pressure above the solution of CO 2 + IL increases linearly with an increase in CO 2 molality. This behavior is observed for the solubility of CO 2 in other types of ILs. Furthermore, the solubility of CO 2 in studied ILs decreases with an increase in temperature.…”
Section: Methodssupporting
confidence: 56%
See 2 more Smart Citations
“…As Figure shows, the pressure above the solution of CO 2 + IL increases linearly with an increase in CO 2 molality. This behavior is observed for the solubility of CO 2 in other types of ILs. Furthermore, the solubility of CO 2 in studied ILs decreases with an increase in temperature.…”
Section: Methodssupporting
confidence: 56%
“…In the studied ILs, the experimental results for the gas solubility are correlated with the extended Henry’s law. The Henry’s constant for CO 2 in ILs are calculated similar to the procedure that was described by Kumelan et al and Perez-Salado et al As Perez-Salado et al have pointed out, the vapor–liquid equilibrium condition for CO 2 + ILs systems results in the extended Henry’s law where K H′CO 2 0 ( T ′ P ) is Henry’s constant of CO 2 in IL based on the molality scale, a CO 2 ( T ′ m C O 2 ) is the activity of CO 2 in the IL, and f CO 2 ( T ′ P ) is the fugacity of CO 2 in the vapor phase. The Henry’s constant of CO 2 in IL is expressed as where K H′CO 2 0 ( T ) is the Henry’s constant of CO 2 in IL at zero pressure, and V m′CO 2 ∞ is the partial molar volume of CO 2 in IL at infinite dilution.…”
Section: Thermodynamic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables S6 and S7 in the Supporting Information summarizes the Henry's constants of gases and ideal selectivities of gas pairs in other physical solvents reported in the literature, including normal ILs and traditional organic solvents . It is found that the solubilities of H 2 S and CO 2 in ChCl + urea mixtures are similar to those in PC but inferior to most other physical solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental data for CH 4 ‐IL systems are summarized in Table . The cations included in the database are bmim and hmim, whereas the anions are BF 4 , CH 3 SO 4 , PF 6 , and Tf 2 N. Experimental data for four ILs with C 2 H 6 , summarized in Table . The cations included in the database are bmim and hmim, whereas the anions are BF 4 , PF 6 , and Tf 2 N.…”
Section: Database Description and Model Developmentmentioning
confidence: 99%